ENT600: Magic Bottle / Nurul Fatihah Mohd Karim, Nur Irdina Mohd Nasri and Suley Norsyakila Yahya - Mohd Karim, Nurul Fatihah; Mohd Nasri, Nur Irdina; Yahya, Suley Norsyakila (2018)
This blueprint recorded the journey of the team from the first meeting till now. From the idea that was generated, we had developing on 'Magic Bottle' for the users. All the descriptions of the service was described deeply in this report. The team had develop the product to a more technological modes where more functions are added to the tools. The team strategies in marketing until the team's promotions are all described in this report. Organisation of the team as well as the financial whereabouts were discussed and reported. This product would be a success as it brings a lot of benefits for its users.